ANALISIS DAN PERANCANGAN SISTEM INFORMASI POSYANDU UNTUK MENDUKUNG SURVEILANS BERBASIS MASYARAKAT - Abu Khoiri (Fakultas Kesehatan Masyarakat, Universitas Jember, 2010)
One of the Alert Village activities is implementation of surveillance based on community namely surveillance of maternal and child health through activities which are conducted at the Integrated Health Services. Surveillance activities are conducted by a cadre who records and reports using information system of the integrated health services. The resulted information is weight, child’s nutritional status, immunization, risk level of pregnant women, immunization of Tetanus Toxoid, list of mothers and children who are either life or lifeless, and presence of health workers during providing services. Based on the previous study, resulted information was difficult to re-access and had not resulted the complete, accurate, and clear information. The objective of this research was to analyze and design of the integrated health services information system for supporting surveillance of maternal and child health based on community at the alert village. Design of this research was qualitative. Development of the system was based on the steps of FAST (Framework for the Application of Systems Thinking). Subjects consisted of both the end users (cadres of the integrated health services, Work Group IV of Family Welfare Education, midwives, and nutritional health workers at Health Centers) and the supporting end users (Head of Village and Chairman of the Alert Village). Data were analyzed using a content analysis (for the qualitative data). The results of this research were scope definition, problem analysis, requirements analysi, logical design, and decision analysis. Keywords : Information System, Integrated Health Services Post, Surveillance of Maternal and Child Health